Anatomic foundations of the pathology and surgery of the anal canal - Rompani, Omar; Bermúdez Villegas, Jorge; Veirano, Gustavo (Cirugía del Uruguay, 1983)
A cellulous subsphincteric space is analyzed by anatomic and surgical studies.